Squarylium‐Triazine Dyad as a Highly Sensitive Photoradical Generator for Red Light. Issue 38 (5th August 2013) - Kawamura, Koichi; Schmitt, Julien; Barnet, Maxime; Salmi, Hanene; Ley, Christian; Allonas, Xavier
Abstract New dyads, based on squarylium dye and substituted‐triazine, were synthesized that exhibit an intramolecular photodissociative electron‐transfer reaction. The compounds were used as a red‐light photoradical generator. The photochemical activity of the dyad was compared to the corresponding unlinked systems (S+T) by determining the rate constant of electron transfer. The efficiency of the radical generation from the dyad compared to the unlinked system was demonstrated by measuring the maximum rate of free radical polymerization of acrylates in film. An excellent relationship between the rate of electron transfer and the rate of polymerization was found, evidencing the interest of this new approach to efficiently produce radicals under red light.